Estudo de tipologias de lajes quanto ao isolamento ao ruído de impacto - Pereyron, Daniel (2008)
The current research focuses on the environmental comfort in the civil construction and refers to a comparative analysis related to the acoustic isolation of reinforced concrete pavement which is submitted to noise of impact. According to thestandards ISO-140/VII, the measurements were taken in situ by using appropriate equipment for this purpose. In order to achieve the aims of this dissertation, unfinished constructions which used different typologies of floor-support (slab) in their structural system were chosen as the object of measurement and, this way, uncovered slabs could be measured. Therefore a better evaluation of their performance was possible and the sound isolation was related to the impact noise, providing evidence of the acoustic isolation. The analysis and interpretation of the results were undertaken through tables and graphs that, according to ISO 717-2, show the performance of each slab and a possible comparison among them. This is also a contributing factor to civil construction professionals as being a working instrument and it serves as a data base for a better understanding towards these materials performance. In this way, minimal values of acoustic comfort may be estimated in a near future.